Evolution of Coastal Works in Portugal and their Interference with Local Morphodynamics - P. Rosa Santos (2009)
Coastal zones are dynamic areas undergoing continuous changes in response to natural and anthropogenic actions. In the paper an overview of the different types of coastal defense works built in Portugal will be presented, giving special attention to their evolution during the last decades, the main problems affecting them, and how experience gathered with previous works has been included in current design practices. The role of numerical models as a mean to understand and to foresee coastal systems' morphodynamics will be also discussed. The importance of numerical modeling as an effective decision Support and design toot will be stressed based on examples from the Portuguese coast. The interference of coastal works with local morphodynamics will also be discussed using GIS techniques applied to Portuguese case studies.